2015
DOI: 10.2134/jeq2014.10.0446
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Fly Ash Incorporation into Cow Dung-Waste Paper Mixtures for Enhanced Vermidegradation and Nutrient Release

Abstract: This study was conducted to establish an appropriate mixture ratio of fly ash (F) to optimized cow dung-waste paper mixtures (CP) to develop a high-quality vermicompost using earthworms (). Fly ash was mixed with cow dung-waste paper mixtures at ratios of (F:CP) 1:1, 1:2, 1:3, 2:1, and 3:1 or CP alone and composted for 14 wk. Olsen P, inorganic N (NO, NO, and NH), C:N ratio, ash content, microbial biomass C, and humification parameters were measured together with scanning electron micrograph images to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…(2010) . Prior to enrichment with rock phosphate, the mixtures were moistened to a moisture content of 60% ± 10, and pre-composted for 1 week to eliminate volatile toxic gases, which are harmful to earthworms ( Mupambwa and Mnkeni, 2015 ). The treatments in this study consisted of different levels of P enrichment applied as igneous rock phosphate i.e.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(2010) . Prior to enrichment with rock phosphate, the mixtures were moistened to a moisture content of 60% ± 10, and pre-composted for 1 week to eliminate volatile toxic gases, which are harmful to earthworms ( Mupambwa and Mnkeni, 2015 ). The treatments in this study consisted of different levels of P enrichment applied as igneous rock phosphate i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The chloroform fumigation–extraction procedure was used for determination of microbial biomass C in compost samples based on the methods of Vance et al. (1987) and as outlined in detail by Mupambwa and Mnkeni (2015) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Before analysis, the dried chicken manure was ground to pass through a 2 mm sieve. The pH and electrical conductivity (EC) were analysed potentiometrically in deionized water at a ratio of 1:10 (w/v) as outlined by Mupambwa and Mnkeni (2015) . Total nitrogen (TN) and total carbon (TC) were determined using the dry combustion method employing a Truspec C/N auto analyser ( LECO, 2003 ).…”
Section: Methodsmentioning
confidence: 99%
“…Such information is required as it could form a basis for development of specialised microbial cocktails for effective bio-conversion of fly ash. Recent studies at the University of Fort Hare in South Africa, using E. fetida and fly ash, cow dung and waste paper mixtures indicated that a 2: 1 (cow dung-waste paper: fly ash) ratio, which gives a C: N ratio of approximately 30, may be the most appropriate, as reflected by rapid decomposition and the increase in extractable P. 50 Fly ash-cow dung compost mixtures may sometimes have less extractable P than cow dung alone. 15 This problem is attributed to microbial community modification as evidenced by very low levels of PSB in fly ash composts.…”
Section: Vermicomposting Of Fly Ashmentioning
confidence: 99%